CALCIUM HYDROXYAPATITE FOR NON-SURGICAL FACIAL REJUVENATION: CASE REPORT (CIPEEX, 2026)
The facial aging process causes changes in volume and support, shape, and texture of all skin layers over time. Calcium hydroxyapatite (CaHA) is a safe and well-established dermal filler with properties that can address some skin alterations by stimulating neocollagenesis. This study is a case report of a 40-year-old patient who underwent facial augmentation and improvement with Radiesse® DUO to maintain ligament restructuring and superficial subcutaneous enhancement. Calcium hydroxyapatite is a biocompatible material that improves skin appearance due to its microspheres, which actively act on the deeper layers of the skin, providing the desired facial volume increase and a tissue-lifting effect.
Keywords: Calcium hydroxyapatite; Calcium hydroxyapatite; facial rejuvenation; facial rejuvenation; facial harmonization; facial harmonization